Multicenter epidemiology of Stenotrophomonas maltophilia bloodstream infections in Indian ICUs: building digital surveillance network - Singh, Parul; Ahmed, M. Nizam; Srivastava, Ashish Kumar; Thakur, Arpan Kumar; Parveen, Rasna; Puraswani, Mamta; Kumar, Subodh; Sagar, Sushma; Soni, Kapil Dev; Aggarwal, Richa; Bindra, Ashish; Goyal, Keshav; et al. (Frontiers in Microbiology, 2025)
BackgroundTo investigate the geospatial epidemiology, clinical features, treatment patterns, and antimicrobial resistance (AMR) trends of Stenotrophomonas maltophilia bloodstream infections (BSIs) in Indian intensive care units (ICUs) participating in a standardized healthcare-associated infection (HAI) surveillance program from 2017 to 2024.MethodsThis retrospective, multicentric study analyzed surveillance data from 54 ICUs across India. Standardized HAI definitions and protocols were applied to characterize infection types, clinical outcomes, and antimicrobial susceptibility.ResultsA total of 271 S. maltophilia isolates were identified, with the highest burden in 2023–24 (n = 76, 28.0%). Central line-associated BSIs (CLABSIs) predominated (64.9%), though their proportion decreased over time, with non-CLABSIs rising from 7.4% (2017–18) to 42.1% (2023–24). Mortality was highest in secondary BSIs (60%), followed by CLABSIs (50.3%) and non-CLABSIs (36.4%). The median ICU stay for CLABSI patients was 21 days. No significant associations were observed between infection type and time to infection or length of stay. High resistance was observed to tobramycin (92%), amikacin (80%), and piperacillin-tazobactam (70%), while trimethoprim-sulfamethoxazole (64.7–94.7%), levofloxacin (93%), and minocycline (94.1%) retained activity.ConclusionS. maltophilia represents a significant ICU pathogen in India, underscoring the urgent need for genomic surveillance and resistance-guided therapeutic strategies.